(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A ligand-H2L complex, with a general formula [M (HL2)2] (M(II)=co, Ni, Cu) was synthesized and characterized for its elementary microelement, metal material, magnetic momentum and molar path measured (M(M)-IR), Fourier-infra-round infrarspectroscopic measurements (MI-IR), ultraviolet-visible spectroscopy (Uv-Vis), molar pathway, and Chl. Tetrahedral geometry for preparing change bases complexes was suggested on the basis of experimental proof. The ligand geometry and its complexes have been verified by their optimized computer studies architectures. A radical of 1.1‐diphenyl-2‐picrylhydrazyl (DPPH) antioxidant activity was tested and contrasted to the usual natural ascorbic acid, antioxidant. So compounds displayed outstanding radical behavior of scavenging.